Expressive Writing Diary Book To Improve Self-Adjustment - Dwi Pertiwi, Fina; Ari Khusumadewi (Bisma The Journal of Counseling, 2022)
The purpose of this study was to create an expressive writing diary as a way to improve the adjustment of seventh grade students at SMP A. Wahid Hasyim Jombang. The research method used is a type of development research with the Borg & Gall model which has 10 steps, namely: 1) research and information gathering, (2) planning, (3) product format development, (4) initial trial, (5) revision product, (6) field trial, (7) product revision, (8) field test, (9) final product revision, and (10) dissemination and implementation. However, with limited time, the researcher only reached stage 5. The results of the material expert test were 88.23%, the media expert test was 92.8%, and the expert test for prospective users was 78.33% so that the overall criteria were very good. , does not need to be revised and good, does not need to be revised. The results of the prototype of the expressive writing diary in the form of a diary with A5 size. The expressive writing diary book media to improve the adjustment of seventh grade students in junior high school has met the product acceptability criteria based on usability, feasibility, accuracy and propriety.